Relationship of health behavior and academic performance among college students implications for University Health Service - Cleofas, Melvin Juan R.; Sana, Erlyn A. (Manila National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2024)
Introduction: The effect on academic performance by students’ health behaviors have been shown by numerous studies. Health behaviors like sleep duration, intake of breakfast, smoking and alcohol use along with stress have shown varied results. This study described the health behaviors of college students and correlated them with their academic performance reflected in their grade weighted average (GWA). Implications on how to educate students about their overall health and promote a healthy university were derived from the results.

Methodology: This is a correlational study. The study was done at a private university offering degree programs in medicine, nursing, medical technology, and physical therapy. From the total student population of 3,105, a stratified random sampling of 385 students were obtained. The online questionnaire and stress inventory was sent to these students initially drawn randomly. However, despite several follow ups and exhausting all measures to achieve the target sample size per college, the student respondents totaled to 174, only those who accomplished the instruments and ended up as convenient samples. Questions pertaining to their health behavior yielded scores on their levels of stress, breakfast intake, sleep duration, smoking and alcohol use that were correlated with their GWA.

Results. Students who participated in the study showed generally healthy behaviors. They sleep from 5 hours a day, take breakfast almost daily, they do not smoke nor drink alcohol. However, they are all moderately to severely stressed due to their academic load. Outstanding grade in this institution is 1.00; so, the closer the GWA of students to 1.00, the better is their academic performance. Students’ overall mean GWA is 2.08, slightly higher among females (x¯ = 2.05), second year students (x¯ = 1.20), and those in nursing (x¯=1.84). The magnitude of correlation between health behaviors and academic performance was negligible and insignificant (p>0.05). There is an inverse correlation between frequency of breakfast intake, sleep duration and academic performance. There is a negligible correlation between frequency of alcoholic intake and frequency of smoking, perceived stress, and academic performance. A serendipitous finding in this study was that there was significant correlation among and in between health behaviors (p<0.05). The students’ health behaviors and academic performance profiles are consistent with the healthy university framework of the Association of Southeast Asian Nations University Network (AUN). In this framework, the center is the overall student wellbeing and presented as a function of the intellectual, health screening, social, emotional and spiritual, as well as physical wellbeing. Results show that the students are academically performing well, practice health behavior although moderately to severely stressed, and the University Health Service really just needs to promote and sustain their well-being through various programs.

Conclusions: Students that participated in the study generally practice good health behaviors. The study showed that there is a negligible correlation between health behavior and academic performance. Nonetheless, the study present generally significant results. Figures suggest that since students practice healthy behaviors, they also perform satisfactorily in their academics.

Recommendations: Health promotion should be emphasized and services available to students like dietary counselling, guidance counselling and infirmary health benefit should be included in the school program.
Thesis
Keywords: Academic performance; Health behaviors; Stress